Corruption and Governance in Nigeria: An Assessment of the Buhari Administration, 2015-2023 - Adenuga, Gbeke Adebowale; Lawal, Akeem Adeniran; Sanusi, Olawale Sefiu (African Journal of Stability and Development (AJSD), 2025)
Nigeria gained independence in 1960 and the global expectation was that the country would experience rapid development, given its human and mineral resources. Over six decades later, the country is yet to break free from the shackles of underdevelopment. A review of the literature on Nigeria shows that corruption and bad governance are mainly responsible for its developmental challenges. The success of Muhammadu Buhari in the 2015 presidential polls was seen as a watershed in the political and developmental annals of the country, given the credibility of the election and the trust reposed in Buhari to make good his electioneering campaign of ridding Nigeria of corruption and to govern according to the dictates of the law. At the end of his second term in office in 2023, Nigeria seemed to be more steeped in corruption with good governance remaining a mirage. Employing the historical approach and with a review of secondary data on the country, the study examined the Buhari Administration (2015-2023) and assessed it poorly in terms of its anti-corruption crusade and adherence to the principles of the rule of law. It found that the administration was more autocratic than preceding administrations and was not sincere in adhering to its promise to curb corruption in the country. The study urged the Nigerian government to develop the will to tackle corruption and govern democratically.